Criminological fiction: what is it good for? - McGregor, Rafe (Journal of Theoretical and Philosophical Criminology, 2020)
The purpose of this article is to establish the criminological value of fiction. I argue for three methodological values of criminological fiction in the context of previous research in the critical realist framework. Criminological fiction is fiction that provides criminological knowledge in virtue of one or more of its phenomenological, counterfactual, or mimetic values, i.e. by (1) representing what certain experiences are like, (2) by representing possible but non-existent situations, and (3) by representing reality in detail and with accuracy. I demonstrate the criminological potential of these values using case studies of a novel, a television series, and a feature film. I conclude that fiction has criminological value and that, in consequence, criminological fiction can provide data that complements data provided by traditional criminological sources.